Prevalence of Cardiovascular Disease and Associated Risk Factors among Adult Population in the Gulf Region: A Systematic Review - Najlaa Aljefree; Faruk Ahmed (Hindawi Limited, 2015)
Background. CVD is a principal cause of mortality and disability globally. Objective. To analyse the epidemiological data on CHD, strokes, and the associated risk factors among adult population in the Gulf countries. Methods. A systematic review of published articles between 1990 and 2014 was conducted. Results. The analysis included 62 relevant studies. The prevalence of CHD was reported to be 5.5% in Saudi Arabia. The annual incidence of strokes ranged from 27.6 to 57 per 100 000 in the Gulf countries with ischaemic stroke being the most common subtype and hypertension and diabetes being the most common risk factors among stroke and ACS patients. The prevalence of overweight and obesity ranged from 31.2% to 43.3% and 22% to 34.1% in males and from 28% to 34.3% and 26.1% to 44% in females, respectively. In males, the prevalence of hypertension and diabetes ranged from 26.0% to 50.7% and 9.3% to 46.8%, respectively; in females these ranged from 20.9% to 57.2% and 6% to 53.2%, respectively. The prevalence of inactivity was from 24.3% to 93.9% and 56.7% to 98.1% in males and females, respectively. Relatively more males (13.4% to 37.4%) than females (0.5% to 20.7%) were current smokers. Available data indicate poor dietary habits with high consumption of snacks, fatty foods, sugar, and fast food. Conclusion. Effective preventative strategies and education programs are crucial in the Gulf region to reduce the risk of CVD mortality and morbidity in the coming years.